Perovskite Solar Cells: Strategically Constructed Bilayer Tin (IV) Oxide as Electron Transport Layer Boosts Performance and Reduces Hysteresis in Perovskite Solar Cells (Small 12/2020). Issue 12 (26th March 2020) - Lin, Liangyou; Jones, Timothy W.; Wang, Jacob Tse‐Wei; Cook, Andre; Pham, Ngoc Duy; Duffy, Noel W.; Mihaylov, Blago; Grigore, Mihaela; Anderson, Kenrick F.; Duck, Benjamin C.; Wang, Hongxia; Pu, Jian; et al.
Abstract : In article 1901466, Bo Chi, Gregory J. Wilson, and co‐workers investigate superior electronic properties of nanostructured tin (IV) oxide (SnO2 ) as an ideal inorganic electron transport layer (ETL) in n–i–p perovskite solar cells. The bilayer ETL architecture attaining impressive power conversion efficiency (PCE) greater than 20% is depicted.